“Will it Catch Their Attention?” – Evaluating Situated and Peripheral Displays in a Personal Context - Güldenpfennig, Florian; Ganhör, Roman; Fitzpatrick, Geraldine (Interaction design & architecture(s), 2015)
Connecting people with technology is an important challenge in HCI and ubiquitous computing. Digital photo frames are a popular class of private situated displays particularly aimed at this purpose. However, their evaluation can be challenging as a significant amount of interaction takes place by looking at the device, i.e., without direct user input. In addition, a photo display can effect people’s perception, without it being at the centre of focussed attention. For tracking use without explicit input and getting a sense of the users’ peripheral perception – and hence the users’ potential awareness of situated displays – we therefore propose a lightweight, unobtrusive and affordable method named Trackaware, drawing on advances in camera hardware and software. We are particularly interested in how researchers and study participants engage with this method and what insights they can obtain. We studied Trackaware involving 61 participants, and our findings suggest that Trackaware can be a strong method for complementing existing evaluation techniques, e.g., in a data triangulation strategy. It should be useful for investigating digital photo frames and other visual peripheral displays, particularly in personal contexts.